(untitled) (Biological Sciences - PJSIR, 2005)
The environmental threat posed by the sugarcane industry is reported. Sixteen effluent samples, from four sites, were collected. These samples were analysed for pH, electrical conductivity (EC), total dissolved solids (TDS), Ca, Mg, Na, K, CO , HCO , Cl, SO , PO , BOD and COD. The results were compared with the National Environmental Quality 3 3 4 4 Standards (NEQS) recommended for the industrial effluent discharge. These effluent samples were further evaluated for irrigation purposes by the TDS, SAR and RSC values and compared with the recommended irrigation water criteria. Results showed that the effluent samples neither met the standards outlined in the NEQS for pH, EC, BOD and COD, nor were they suitable for irrigation purposes due to the TDS values higher than those recommended for irrigation.